Abandoned boats contribute to spread of Aedes and Culex vector mosquitoes in coastal belt, Galle District, Southern Sri Lanka - Dinithi Shamalee Dissanayake; Chandana Dammika Wijekoon; Hemantha Wegiriya (Journal of Vector Borne Diseases, 2022)
Background & objectives: Although, the number of considerable cases of dengue and lymphatic filariasis have been reported from Galle District, Sri Lanka in the past several years, contribution of abandoned boats to spread vector mosquitoes of Aedes and Culex in the coast is not well studied. Our aim was to assess the positive composition of different types of abandoned boats by larval vector mosquitoes to investigate their occurrence and habitat preference, and the monsoonal and co-existence variation of Aedes mosquitoes. Methods: The 4th instar larvae of Aedes and Culex species from three different abandoned boat types in nine subsampling sites at three municipal areas in Galle District were collected during 2017–2019. In total, 15 sampling rounds were conducted in each site for three years duration as five sample rounds per year. Larval collections and identifications were carried out using standard techniques and identification keys according to WHO guidelines. The occurrence of mosquito larvae was analysed by boat type, locations within area and year. Further, the average infestation variation of Aedes mosquitoes were compared with monsoonal and co-existence changers. Results; Out of the total abandoned boats, majority (51%) were engine boats and, 32.7%, 16.35% were troller boats and canoe boats, respectively. Troller boats were highly infested boat type for vector mosquitoes. Aedes albopictus was the dominant vector in abandoned boats other than recorded Ae. aegypti and Culex quinquefasciatus. Culex quinquefasciatus showed comparatively low infestation percentages. The average infestation of Ae. albopictus showed a consistent pattern with monsoon variation. A competitive rapid invasion of Aedes aegypti was observed with the suppressing Ae. albopictus in abandoned boats after 2018. Interpretation & conclusion: Abandoned boats contribute noteworthy to spread of Aedes and Culex vector mosquitoes in coastal belt, Galle District. These study findings would be helpful for researchers and health authorities to design appropriate vector control measures and to mitigate future dengue and filariasis outbreaks.